Cathode paste composition and battery cathode prepared therefrom
Patent Information
- Application Number
- CN202610526861.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-21
- Filing Date
- 2026-04-21
- Publication Date
- 2026-10-23
AI Technical Summary
然而,PVDF本身可能对金属集流体(例如铝)的粘附力不足,从而导致操作过程中分层、开裂或电接触损失
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a cathode in a rechargeable battery, and more specifically, to the use of a hydrogenated styrene-based block copolymer as a cathode layer and a binder in a slurry composition for the battery. Background Technology
[0002] Rechargeable batteries are used to power a variety of applications, including mobile phones, laptops and tablets, power tools, energy storage systems, and electric vehicles. Examples of rechargeable batteries include lithium-ion batteries, sodium-ion batteries, and other alkaline-ion battery systems. A typical battery includes a cathode (positive electrode), an anode (negative electrode), a separator, and an electrolyte. The cathode is formed by coating a slurry containing active materials, binders, and conductive materials onto a current collector, followed by drying and optionally compression.
[0003] Polyvinylidene fluoride (PVDF) is commonly used as a binder in cathodes due to its chemical stability and compatibility with a variety of cathode active materials. However, PVDF itself may have insufficient adhesion to metal current collectors (such as aluminum), leading to delamination, cracking, or loss of electrical contact during operation. PVDF-based slurries may also exhibit suboptimal rheological properties, including poor dispersion of solid components, insufficient precipitation of active materials, and inadequate shear thinning behavior, resulting in coating defects and processing challenges, especially under high solids loads.
[0004] Therefore, there is still a need for an improved binder composition to provide enhanced adhesion and slurry processability. Invention Overview
[0005] In one aspect, a cathode for a battery is disclosed. The cathode includes a current collector and a cathode layer disposed on the current collector. The cathode layer comprises an active material, a conductive material, and a binder composition. The binder composition comprises, is substantially composed of, or is composed of PVDF and a hydrogenated styrene-based block copolymer (HSBC) component, the component comprising a first HSBC having at least one of the general formulas selected from AMA, (AMA)nX, (AM)nX, and mixtures thereof, where n is an integer from 2 to 7, X is a coupling agent residue, each A block consists of a vinyl aromatic unit, and each M block consists of at least one conjugated diene unit and at least one vinyl aromatic unit. The aromatic block index of the M block is determined by HSQC NMR spectroscopy to be 3-40%. The peak molecular weight (Mp) of the first HSBC is 80-150 kg / mol, and the polystyrene content is 20-70 wt%. The weight ratio of PVDF to HSBC is 4:6-15:1. According to ASTM D903, the peel adhesion strength of the cathode layer to the current collector is >0.5 N / 25 mm, wherein the peel test is carried out at a peel rate of 200 mm / min.
[0006] In one aspect, a cathode paste is disclosed. The cathode paste comprises an active material, a conductive material, and a binder composition. The binder composition comprises, is substantially composed of, or is composed of PVDF and an HSBC component, wherein the HSBC component comprises a first HSBC having at least one of the general formulas selected from AMA, (AMA)nX, (AM)nX, and mixtures thereof, where n is an integer from 2 to 7, X is a coupling agent residue, each A block consists of a vinyl aromatic unit, and each M block consists of at least one conjugated diene unit and at least one vinyl aromatic unit. The aromatic block index of the M block is determined by HSQCNMR spectroscopy to be 3-40%. The peak molecular weight (Mp) of the first HSBC is 80-150 kg / mol, and the polystyrene content is 20-70 wt%. The weight ratio of PVDF to HSBC is 4:6-15:1. The paste has at least one of the following properties: according to ASTM D2196 at 21-25°C and 40 s... -1 The viscosity, measured at the shear rate, was 2000-15000 cP, the solid content was 30-75 wt%, and the grinding fineness was no greater than 10 µm.
[0007] In one aspect, the cathode is used in lithium-ion batteries, sodium-ion batteries, and other rechargeable battery systems. Invention Details
[0008] The following terms will be used throughout the specification.
[0009] "consistently made of" means that the claimed composition mainly contains the specified material and may contain additional components that do not materially affect the novel characteristics or function of the claimed invention, and if present, the content of said additional components should be <30%, <20%, or <10%.
[0010] "At least one of A, B, and C" or "any one of A, B, and C" means a single member, more than one member, or a combination of members. For example, "at least one of A, B, and C" includes, for example, only A, only B, or only C, as well as A and B, A and C, B and C, or A, B, and C, or any other combination of A, B, and C.
[0011] An implementation plan listed in the form of "A, B or C" should be understood to include implementation plans that contain only A, only B, only C, "A or B", "A or C", "B or C" or "A, B or C".
[0012] "Any one of A, B or C" refers to one of the options A, B or C.
[0013] "Any one of A, B, and C" refers to one or more options from A, B, and C.
[0014] "Copolymer" refers to a polymer derived from a variety of monomeric substances.
[0015] A "block copolymer" is a copolymer containing multiple monomeric substances, wherein the monomers exist in the form of blocks. Each block consists of a set of monomeric units, which are different from the set of monomers in the surrounding blocks connected in the same block copolymer. Each block can be composed of homopolymers or random copolymers.
[0016] The "polystyrene content" or "PSC" of a block copolymer refers to the weight percentage of vinyl aromatics (e.g., styrene) in the block copolymer, calculated by summing the molecular weights of all vinyl aromatic units and dividing by the total molecular weight of the block copolymer. PSC can be determined using any suitable method, such as proton nuclear magnetic resonance (NMR). 1 H NMR).
[0017] "Butene unit content" refers to the content of butene units (B) relative to all dienyl units in a given polymer (e.g., a hydrogenated block copolymer), expressed in wt%. Butene units are formed by the 1,2-addition polymerization of 1,3-butadiene monomers followed by hydrogenation. 1,3-butadiene monomers can also be polymerized by 1,4-addition polymerization, followed by hydrogenation to produce ethylene units (E). Both butene and ethylene units can be present in hydrogenated block copolymers, which may also contain vinyl aromatic units arranged in any order and / or other units derived from conjugated diene monomers. The butene unit content can be determined by... 1 H NMR and 13 C NMR determination.
[0018] "Molecular weight" or Mw refers to the polystyrene equivalent molecular weight of a polymer block or block copolymer, expressed in g / mol. Mw can be determined using gel permeation chromatography (GPC) with polystyrene calibration standards, for example, according to ASTM 5296. The GPC detector can be an ultraviolet or refractive index detector or a combination thereof. The chromatograph is calibrated using commercially available polystyrene molecular weight standards. The Mw of such calibrated polymers, determined using GPC, is the polystyrene equivalent molecular weight or apparent molecular weight. The Mw expressed herein is determined at the peak of the GPC trace and is commonly referred to as the polystyrene equivalent "peak molecular weight," denoted as Mp.
[0019] "Hydrogenated styrene block copolymer" or "HSBC" refers to a partially or fully hydrogenated styrene block copolymer. HSBC is based on blocks of conjugated dienes and styrene monomers, wherein a portion of the double bonds generated by the conjugated diene units have been reduced or hydrogenated. HSBC is hydrogenated to a hydrogenation level of >80%, >90%, >95%, or >99%. In some embodiments, the aromatic bonds have been reduced or hydrogenated to a hydrogenation level of 0-15%.
[0020] "Hydrogenated styrene block copolymer component" or "HSBC component" refers to one or more hydrogenated styrene block copolymers present in the binder, including a first HSBC and an optional second HSBC.
[0021] "Hydrogenation level" (H2%) refers to the saturation level of the olefin double bonds in the block copolymer, which can be determined using proton nuclear magnetic resonance (¹H NMR) spectroscopy or carbon-13 nuclear magnetic resonance (C-13 NMR). 13 The determination is performed by C NMR spectroscopy and / or ozone decomposition titration.
[0022] "Residual unsaturation (RU)" refers to the level of unsaturation, specifically the number of carbon-carbon double bonds per gram of block copolymer. RU can be measured using nuclear magnetic resonance (NMR). 1 The determination is performed by ¹H NMR or ozone decomposition titration.
[0023] A "unit" refers to a block of structures derived from a monomer after polymerization, representing a repeating entity that forms part of a polymer or copolymer chain. Unlike the single molecule of "monomer" before polymerization, a "unit" is a transformed version of the monomer after the polymerization process. Polymerized units can be further transformed into hydrogenated or functionalized units.
[0024] The glass transition temperature (Tg) was determined by dynamic mechanical analysis (DMA) according to ASTM 4065.
[0025] "Binder composition" refers to a polymer binder system containing PVDF and HSBC components. The binder composition is present in the cathode slurry and, after drying, in the cathode layer.
[0026] "Thin film" can be used interchangeably with "layer" or "film layer".
[0027] "Electrolyte absorption rate" refers to the increase in mass of a polymer-containing film or layer after immersion in an electrolyte, expressed as a percentage relative to its initial dry weight. The electrolyte absorption rate is determined by measuring the weight of the film or layer before and after immersion in the electrolyte, and reflects solvent absorption, polymer-electrolyte compatibility, and dimensional stability in the electrochemical environment.
[0028] "Thickness increase rate" refers to the percentage increase in film thickness relative to the initial thickness of the dry film before electrolyte exposure. The film thickness before and after immersion can be determined using a micrometer or profilometer. The electrolyte can be, for example, 1.0 M LiPF6 in a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) in a 1:1:1 volume ratio.
[0029] This invention relates to cathode and slurry compositions for rechargeable batteries. The cathode includes a cathode layer disposed on a current collector, wherein the cathode layer is formed from a cathode slurry composition comprising a binder, an active material, a conductive material, and a solvent. The binder comprises, is substantially composed of, or is composed of hydrogenated styrene-based block copolymer components and polyvinylidene fluoride (PVD).
[0030] Binder composition: Based on the total weight of the cathode slurry composition, the binder composition is used in the cathode slurry composition and the cathode layer formed therefrom in an amount of <10 wt%, or <5 wt%, or 1-10 wt%, or 1-8 wt%, or 1-6 wt%, or 1-5 wt%. In some embodiments, PVDF and hydrogenated styrene-based block copolymer components (HSBC components) are present in the binder in a PVDF to HSBC component weight ratio ranging from 4:6-15:1, or 4:6-12:1, 4:6-10:1, or 4:6-9:1, or 5:5-9:1, or 6:4-9:1, or 6.5:3.5-9:1, or 7:3-9:1, or 8:1-12:1.
[0031] In some embodiments, the HSBC component consists of a single HSBC (first HSBC). In other embodiments, the HSBC component also includes one or more HSBCs different from the first HSBC (second HSBC). In some embodiments, the HSBC component comprises two HSBCs in a weight ratio of first HSBC to second HSBC ranging from 1:1 to 3:1, or 1.2:1 to 2.5:1, or 1.5:1 to 2:1. In some embodiments, the combined amount of the first HSBC and the second HSBC corresponds to the total HSBC component in the adhesive.
[0032] First hydrogenated styrene-based block copolymer (HSBC): The first HSBC comprises a block copolymer having a structure selected from AMA, (AMA)nX, (AM)nX, and mixtures thereof, where n is an integer from 2 to 7 and X is a residue of a coupling agent. The first HSBC is formed by hydrogenating a styrene-based block copolymer (SBC) precursor, which may be linear, branched, or radial. The first HSBC may be partially or fully hydrogenated.
[0033] Each A block consists of a vinyl aromatic unit. Each M block contains at least one conjugated diene unit and at least one vinyl aromatic unit.
[0034] In some embodiments, the aromatic block index, or "ABI," of the M-block is 3-40% or 3-35%, which is the percentage of vinyl aromatic units in the polymer chain whose two nearest-neighbor positions are both vinyl aromatic units, relative to the total aromatic units present in the M-block. The ABI can be determined using heteronuclear single quantum coherence (HSQC) NMR spectroscopy. The following non-limiting examples illustrate the determination of the ABI within the M-block in representative M-blocks or HSBC structures, where S represents a vinyl aromatic unit and "bd" represents a conjugated diene-derived unit. A qualified vinyl aromatic unit with vinyl aromatic neighbors on both sides is indicated by lowercase (s), while a vinyl aromatic unit is indicated by S.
[0035] Example 1 (M block): bd-bd-SsS-bd-SsS-bd-SsS-bd-bd. The total number of vinyl aromatic units is 9; when ABI=3 / 9, the qualified units are 3.
[0036] Example 2 (M block): bd-bd-SsS-bd-S-bd-SsS-bd-bd. The total number of vinyl aromatic units is 7; when ABI=2 / 7, the number of qualified units is 2.
[0037] Example 3 (M block): bd-bd-SssssS-bd-S-bd-SsS-bd-bd. The total number of vinyl aromatic units is 10; when ABI=5 / 10, the number of qualified units is 5.
[0038] Example 4 (M block): bd-bd-SS-bd-SsS-bd-SsS-bd-bd. The total number of vinyl aromatic units is 8; when ABI=2 / 8, the number of qualified units is 2.
[0039] Example 5 (HSBC(AM)nX structure): (SSSSSSS-bd-bd-SsS-bd-SsS-bd-bd)nX. Only the M block is considered. The total number of vinyl aromatic units in the M block is 9; when ABI=3 / 9, the qualified units are 3.
[0040] Example 6 (HSBC with AMA structure): SSSSSSS-bd-bd-SsS-bd-SsS-bd-bd-SSSSSS. Only the M block is considered. The total number of vinyl aromatic units in the M block is 9; when ABI=3 / 9, the qualified units are 3.
[0041] In some embodiments, the M block corresponds to an E / B / S or EP / S type copolymer block. In these embodiments, the E / B / S block is a copolymer block composed of ethylene units, butene units, and vinyl aromatic units, and the EP / S block is a copolymer block composed of ethylene-propylene units and vinyl aromatic units. Vinyl aromatic monomers can be introduced into the M block in any order or distribution by copolymerization with conjugated diene monomers (e.g., 1,3-butadiene or isoprene) to form the structure described herein. In some embodiments, the E / B / S and EP / S copolymer blocks exhibit a distribution consistent with the M block distribution described above.
[0042] The first HSBC has a configuration selected from the following: SE / B / SS, S-EP / SS, (SE / B / SS)nX, (SE / B / S)nX, (S-EP / SS)nX, and (S-EP / S)nX, and mixtures thereof, where n is an integer from 2 to 7, and X is a residue of the coupling agent. These configurations correspond to AMA, (AMA)nX, and (AM)nX structures, respectively. The first HSBC may be partially or fully hydrogenated.
[0043] Each S block consists of vinyl aromatic units. E / B / S consists of ethylene (E) units / butene (B) units / vinyl aromatic (S) units. Each EP / S consists of ethylene-propylene (EP) units / vinyl aromatic (S) units. In some embodiments, vinyl aromatic monomers may be introduced or copolymerized with 1,3-butadiene monomers and / or isoprene monomers in any order and distribution to form any of the aforementioned configurations. In some embodiments, the E / B / S and EP / S copolymers are copolymers with a non-uniform monomer distribution. In some embodiments, the ABI of the M block (e.g., the E / B / S and EP / S copolymer block) is 3-40%, or 3-35%, determined by HSQC NMR spectroscopy, which is the percentage of vinyl aromatic units in the polymer chain whose two nearest neighbor positions are both vinyl aromatic units, relative to the total aromatic units present in the M block.
[0044] In some embodiments, the vinyl aromatic monomer is selected from styrene, α-methylstyrene, p-methylstyrene, p-ethylstyrene, p-n-propylstyrene, p-isopropylstyrene, p-n-butylstyrene, p-sec-butylstyrene, p-isobutylstyrene, p-tert-butylstyrene, isomers of p-decylstyrene, isomers of p-dodecylstyrene, ortho-substituted styrene, meta-substituted styrene, 1,1-diphenylethylene, dimethylstyrene, halogenated styrene, methoxystyrene, acetoxystyrene, vinyltoluene, isomers of vinyltoluene, vinylxylene, 4-vinylbiphenyl, vinylnaphthalene, vinylanthracene, and mixtures thereof. In some embodiments, the vinyl aromatic monomer is styrene. As used herein, "vinyl aromatic unit" refers to a polymerization unit derived from a vinyl aromatic monomer, including such units when block copolymer segments are introduced.
[0045] In some implementations, the PSC of the first HSBC is >20wt%, or <60wt%, or <50wt%, or 20-70wt%, or 20-55wt%, or 25-50wt%, or 30-45wt%.
[0046] In some embodiments, the butene unit content of the first HSBC is >20wt%, or >25wt%, or >30wt%, or >35wt%, or <80wt%, or 20-80wt%, or 25-80wt%, or 30-80wt%.
[0047] In some embodiments, the M-block polystyrene content of the first HSBC is 20-65 wt%, or 35-65 wt%, or 40-65 wt%, or 40-60 wt%, based on the total weight of the M blocks (E / B / S and EP / S).
[0048] In some implementations, the peak molecular weight (Mp) of the first HSBC is 80-150 kg / mol, or 90-140 kg / mol, or 100-130 kg / mol.
[0049] In some implementations, the diblock content of the first HSBC is <15wt%, or <10wt%, or <7wt%, or 1-15wt%, or 1-10wt%, or 1-7wt%, based on the total weight of the first HSBC.
[0050] In some embodiments, the first HSBC has a SE / B / SS, (SE / B / SS)nX, or (SE / B / S)nX structure, wherein the E to B molar ratio of the E / B / S blocks is 10:90-65:35, or 20:80-60:40, or 25:75-55:45, which can be achieved through... 1 H NMR determination. In some embodiments, the E to P molar ratio of the copolymer EP / S is 1:1.
[0051] In some implementations, the weight ratio of the S cell to the E / B / S cell and / or the S cell to the EP / S cell of the first HSBC is 20:80-55:45, or 25:75-50:50, or 30:70-45:55, based on the total weight of the first HSBC.
[0052] In some embodiments, the first HSBC has a SE / B / SS, (SE / B / SS)nX, or (SE / B / S)nX structure, wherein, based on the total weight of the first HSBC, the S-block comprises 10-25 wt%, or 12-22 wt%, or 14-20 wt%, or 16-18 wt%, and the E / B / S block comprises 50-80 wt%, or 55-75 wt%. In some embodiments, the first HSBC has a S-EP / SS, (S-EP / SS)nX, and (S-EP / S)nX structure, wherein the S-block comprises 10-25 wt%, or 12-22 wt%, or 14-20 wt%, or 16-18 wt%, and the EP / S block comprises 50-80 wt%, or 55-75 wt%, based on the total weight of the first HSBC.
[0053] In some embodiments, the first HSBC has a structure of SE / B / SS, (SE / B / SS)nX, or (SE / B / S)nX, wherein, based on the total weight of the 1,3-butadiene monomers polymerized in the E / B / S block, the E / B / S block contains 15-50 wt%, or 18-45 wt%, or 20-40 wt% of 1,3-butadiene monomers introduced via 1,2-addition, with the remainder being 1,4-addition.
[0054] In some embodiments, the first HSBC has a structure of S-EP / SS, (S-EP / SS)nX, or (S-EP / S)nX, wherein the total polymerized isoprene monomer in the EP block comprises >55 wt%, or >65 wt%, or >70 wt%, or >80 wt%, or >90 wt%, or <100 wt% of polymerized isoprene monomer introduced and hydrogenated by 1,4-addition, with the remainder being 3,4-addition.
[0055] The S-blocks derived from the polymerized vinyl aromatic monomer units remain substantially unhydrogenated. In some embodiments, the hydrogenation level of block S is <30%, or <20%, or <10%, or <5%, based on the total double bonds present in the S-block. In some embodiments, the polybutadiene block is hydrogenated to a hydrogenation level of >80%, or >85%, or >90%, or >95%, or >98%, or >99%, or up to 100%, based on the total double bonds present in the polybutadiene block. In some embodiments, the polyisoprene block is hydrogenated to a hydrogenation level of >80%, or >85%, or >90%, or >95%, or >98%, or >99%, or up to 100%, based on the total double bonds present in the polyisoprene block.
[0056] In some embodiments, the residual unsaturation or RU of the first HSBC is 0-20 meq / g, or 0-15 meq / g, or 0-10 meq / g. In some embodiments, when the first HSBC is partially hydrogenated, the residual unsaturation or RU of the hydrogenated polybutadiene block is <20 meq / g, or <15 meq / g, or <10 meq / g, or <8 meq / g, or >3 meq / g, or >5 meq / g, or 3-20 meq, or 3-15 meq / g, or 3-10 meq / g. In some embodiments, when the first HSBC is fully hydrogenated, the residual unsaturation or RU of the hydrogenated polybutadiene block is 0-3 meq / g, or 0-2 meq / g, or 0-1 meq / g, or 0-0.5 meq / g, or 0.05-0.5 meq / g, or <0.5 meq / g, or <0.4 meq / g, or <0.3 meq / g, or <0.02 meq / g, or <0.1 meq / g, based on the total double bonds present in the polybutadiene block.
[0057] In some embodiments, the peak molecular weight of each S-block is 4-45 kg / mol, or 5-40 kg / mol, or 7-35 kg / mol, or 9-30 kg / mol, or at least 9.0 kg / mol, or at least 6 kg / mol, or at least 4.0 kg / mol. In some embodiments, the peak molecular weight of the E / B / S block is 26-105 kg / mol, or 30-95 kg / mol, or 45-75 kg / mol, or 55-65 kg / mol. In some embodiments, the peak molecular weight of the E / B / S block is determined by subtracting the peak molecular weight of the S-block from the peak molecular weight of the SE / B / S block.
[0058] In some implementations, the first HSBC having a (SE / B / S)nX, (SE / B / SS)nX, or (SE / P / S)nX configuration has a coupling efficiency of >50%, or >60%, or >70%, or >80%, or >90%.
[0059] In some implementations, the tensile strength of the first HSBC is >10 MPa, or >15 MPa, or <50 MPa, or <40 MPa, or 10-50 MPa, or 10-40 MPa, or 15-35 MPa, as determined according to ASTM D638.
[0060] In some implementations, the first HSBC exhibits electrochemical stability suitable for lithium-ion battery cathodes. For example, linear sweep voltammetry (LSV) measurements show that the first HSBC, relative to Li / Li +The electrochemical stability is at least approximately 4.5 V, as evidenced by the absence of a significant oxidation current. This electrochemical stability indicates that the first HSBC is suitable for cathode environments using high-voltage non-aqueous electrolytes.
[0061] In some embodiments, the first HSBC is modified by grafting with maleic anhydride, wherein maleic anhydride is an unsaturated monomer containing anhydride functional groups. Maleic anhydride is chemically grafted onto the first HSBC (including styrene blocks, ethylene-butene blocks, or ethylene-propylene blocks) to form a maleicated (first) HSBC. Suitable maleic anhydride-modified HSBCs and grafting techniques are disclosed in U.S. Patents US4,946,899, US7,169,848, US4,578,429, US5,506,299, and US4,292,414, each of which is incorporated herein by reference. In some embodiments, based on the total weight of the first HSBC, the first HSBC contains 0.02-20 wt%, or 0.1-10 wt%, or 0.2-5 wt%, or 0.5-3 wt%, or >0.5 wt%, <5 wt%, or <10 wt%, or <15 wt%, or <20 wt% of maleic anhydride functional groups as the grafted portion.
[0062] Second hydrogenated styrene block copolymer: In some embodiments, the second HSBC comprises a block copolymer having a structure AD, wherein A is a vinyl aromatic block, D is composed of at least one conjugated diene, wherein the conjugated diene includes, but is not limited to, butadiene and isoprene, and the D block does not contain a vinyl aromatic unit.
[0063] In some embodiments, the D block is composed of isoprene. Upon hydrogenation, the isoprene-derived block forms a saturated rubber block comprising an ethylene-propylene unit. The composition of the ethylene-propylene block reflects the microstructure of the isoprene unit before hydrogenation, including its introduction via 1,4-addition and optionally 3,4-addition.
[0064] In some embodiments, the D block is composed of butadiene. Upon hydrogenation, the butadiene-derived block forms a saturated rubber block comprising ethylene (E) and butene (B) units. The composition of the ethylene-butene block reflects the microstructure of the butadiene unit prior to hydrogenation, including the introduction of 1,2-addition and 1,4-addition. Hydrogenation of the 1,2-addition unit yields a butene unit, while hydrogenation of the 1,4-addition unit yields an ethylene unit. The relative ratio of ethylene to butene units can be controlled by the polymerization conditions and is reflected in the butene unit content of the polymer.
[0065] In some embodiments, the second HSBC has a structure selected from SE / B, S-EP, and mixtures thereof. The second HSBC may be partially or fully hydrogenated.
[0066] Each S block consists of a vinyl aromatic unit. E / B consists of an ethylene (E) unit / butene (B) unit. Each EP consists of an ethylene-propylene (EP) unit.
[0067] In some embodiments, the vinyl aromatic monomer is selected from styrene, α-methylstyrene, p-methylstyrene, p-ethylstyrene, p-n-propylstyrene, p-isopropylstyrene, p-n-butylstyrene, p-sec-butylstyrene, p-isobutylstyrene, p-tert-butylstyrene, isomers of p-decylstyrene, isomers of p-dodecylstyrene, ortho-substituted styrene, meta-substituted styrene, 1,1-diphenylethylene, dimethylstyrene, halogenated styrene, methoxystyrene, acetoxystyrene, vinyltoluene, isomers of vinyltoluene, vinylxylene, 4-vinylbiphenyl, vinylnaphthalene, vinylanthracene, and mixtures thereof. In some embodiments, the vinyl aromatic monomer is styrene.
[0068] In some implementations, the peak molecular weight (Mp) of the second HSBC is 100-250 kg / mol, or 110-250 kg / mol, or 120-240 kg / mol.
[0069] In some embodiments, the butene unit content of the second HSBC is >20wt%, or >25wt%, or >30wt%, or >35wt%, or <80wt%, or 20-80wt%, or 25-80wt%, or 30-80wt%.
[0070] In some implementations, the polystyrene content of the second HSBC is 30-60 wt%, or 30-55 wt%, or 35-50 wt%, or 36-48 wt%.
[0071] Polyvinylidene fluoride (PVDF): The binder contains PVDF, a semi-crystalline fluoropolymer, which provides chemical stability, film-forming ability and mechanical integrity to the cathode layer.
[0072] In some embodiments, the PVDF comprises units derived from vinylidene fluoride and one or more other monomers, such as (i) (meth)acrylic acid and / or (ii) (meth)acrylate hydroxyalkyl esters. Examples of (meth)acrylic acid include acrylic acid, methacrylic acid, or mixtures of both. (Meth)acrylate hydroxyalkyl esters may have C1-C5 alkyl chains, such as hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, or 2-hydroxybutyl (meth)acrylate.
[0073] In some embodiments, the weight-average molecular weight of PVDF is 50,000-8,000,000 g / mol. In some cases, the molecular weight may be 50,000-6,500,000 g / mol, or 50,000-5,000,000 g / mol, or 50,000-3,000,000 g / mol, or 50,000-1,500,000 g / mol, or 500,000-1,500,000 g / mol.
[0074] In some embodiments, PVDF includes modified PVDF materials. These modified PVDF binders may comprise copolymers of vinylidene fluoride with one or more comonomers, said comonomers including hexafluoropropylene (HFP), chlorotrifluoroethylene (CTFE), (meth)acrylic acid monomers (e.g., acrylic acid or methacrylic acid), or (meth)acrylic acid hydroxyalkyl esters having C1-C5 hydroxyalkyl groups.
[0075] Active materials: Cathode active materials suitable for cathode layer and cathode paste compositions include intercalation or intercalation active materials capable of undergoing reversible electrochemical reactions with alkali ions.
[0076] In some embodiments, this cathode active material comprises lithium-containing transition metal oxides, phosphates, or mixed metal compounds. Examples include lithium cobalt oxide (LiCoO2, LCO) and lithium nickel manganese cobalt oxide (LiNi). x Mn γ CozO2, NMC), lithium nickel cobalt aluminum oxide (LiNi) x Co γ AlzO2 (NCA), lithium manganese oxide (LiMn2O4, LMO), lithium iron phosphate (LiFePO4, LFP), lithium-rich layered oxides, lithium titanium oxide (Li4Ti5O4) 12 ), lithium vanadium phosphate (Li3V2(PO4)3) and other lithium-containing transition metal oxides or mixed metal oxides.
[0077] In a further embodiment, the cathode active material comprises sodium-containing transition metal oxides, phosphates, Prussian blue analogs, or mixed metal compounds suitable for sodium-ion batteries.
[0078] In some embodiments, the active material in the cathode slurry composition is 80-98 wt%, or at least 85 wt%, or at least 90 wt%, based on the total weight of the cathode slurry composition.
[0079] Conductive material: The conductive material suitable for the cathode layer of a rechargeable battery includes any conductive material as long as it does not cause a chemical change. Examples of the conductive material include one or more of carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, metal powder) or metal-based materials (e.g., metal fibers comprising copper, nickel, aluminum, silver, or mixtures thereof).
[0080] In some embodiments, the conductive material in the cathode paste composition is 1-10 wt%, or 1-5 wt%, or at least 2 wt%, or at least 3 wt%, or <10 wt%, based on the total weight of the cathode paste composition.
[0081] Solvent: The cathode paste contains a solvent for dissolving or dispersing the binder during electrode fabrication. Examples include nitrogen-containing organic solvents (e.g., N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, dimethylformamide, dimethylacrylurea, γ-butyrolactone, and dimethylacetamide), common low-boiling organic solvents (including ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as tetrahydrofuran and dioxane), and mixtures of the above substances.
[0082] Methods for preparing cathode slurry and cathode layer: The cathode slurry is prepared by dissolving a binder composition containing PVDF and HSBC components in a solvent, and then mixing and dispersing the active and conductive materials in the binder solution. Alternatively, the slurry can be prepared by mixing a binder composition of a solid general form, the active material, and the conductive material, then adding a solvent and mixing to form a dispersion.
[0083] In some embodiments, the PVDF and HSBC components may be dissolved together or separately in a solvent at an ambient temperature or high temperature sufficient to dissolve each component. In some embodiments, the HSBC component is dissolved at 70-100°C, 75-95°C, or 80-90°C. In some embodiments, the concentration of polymer solids (PVDF and HSBC components) in the adhesive solution is 5-15 wt%, 5-10 wt%, or 8-10 wt%, based on the total weight of the adhesive solution.
[0084] The active and conductive materials are combined and mixed with the binder components in solution to form a cathode slurry. The order of addition can vary, and mixing can be carried out using any suitable technique (including batch or continuous processes) to obtain a uniform dispersion.
[0085] In some embodiments, the cathode paste comprises an active material: conductive material: PVDF:HSBC component in a mass ratio of 72:4.0:3.6:0.4 to 108:6.0:5.4:0.6, or 76.5:4.25:3.825:0.425 to 103.5:5.75:5.175:0.575, or 81:4.5:4.05:0.45 to 99:5.5:4.95:0.55, or 85.5:4.75:4.275:0.475 to 94.5:5.25:4.725:0.525.
[0086] Additional solvents can be added during the mixing process to promote dispersion and adjust the viscosity of the slurry for coating.
[0087] In some embodiments, the solid content of the cathode slurry is at least 30 wt%, or >35 wt%, or >40 wt%, or <90 wt%, or <80 wt%, or <75 wt%, or <70 wt%, or 30-75 wt%, or 30-65 wt%, or 40-75 wt%, or 40-60 wt%, based on the total weight of the slurry.
[0088] In some embodiments, the cathode layer is prepared by applying the cathode paste onto a current collector. Suitable current collectors include conductive metal substrates in the form of foils, meshes, or patterned sheets, such as aluminum. In some embodiments, the current collector has a thickness of 5-30 µm and is optionally treated, roughened, or coated to improve adhesion.
[0089] The cathode slurry can be applied to one or both sides of the current collector using coating techniques selected from blade coating, stencil coating, transfer coating, spraying, roller coating, dip coating, and curtain coating. The coating thickness can be 10–300 µm, 20–200 µm, or 50–120 µm.
[0090] After coating, the film is dried to remove the solvent and form a cathode layer.
[0091] The dry cathode layer can be compressed to increase its density. In some embodiments, the compacted density of the cathode layer is 1.6-2.0 g / cm³.
[0092] Binder performance: The binder composition can be evaluated independently of the cathode by forming a thin film and measuring the physical and electrochemical properties related to electrolyte interaction and stability.
[0093] In some embodiments, the film formed from the binder composition exhibits an electrolyte absorption rate of 5-20 wt%, 6-15 wt%, or 7-15 wt% after being immersed in an electrolyte at room temperature for 24 hours.
[0094] Slurry performance: In some embodiments, cathode slurries containing PVDF and HSBC components exhibit shear-thinning behavior and improved rheological properties compared to slurries containing only PVDF, thereby contributing to the dispersion of solid components, slurry stability and coating uniformity.
[0095] In some embodiments, the cathode paste composition is tested according to ASTM D2196, and the cathode paste composition is effective in 40 seconds. -1 The viscosity at the shear rate and ambient temperature (e.g., 21-25°C) is 2,000-15,000 cP, or 2,000-11,000 cP, or 2,000-10,000 cP, or 3,000-10,000 cP, or 3,000-9,500 cP, or 4,000-9,500 cP.
[0096] In some implementations, according to ASTM D2196, the cathode paste composition with a solid content of 45 wt% is tested for 40 seconds. -1 The viscosity at the shear rate and ambient temperature (e.g., 21-25°C) is 2,000-6,000 cP, or 3,000-6,000 cP, or 4,000-5,500 cP.
[0097] In some implementations, according to ASTM D2196, a cathode paste composition with a solid content of 47.4 wt% is tested for 40 seconds. -1 The viscosity at the shear rate and ambient temperature (e.g., 21-25°C) is 7,000-11,000 cP, or 7,000-10,000 cP, or 8,000-10,000 cP, or 8,500-9,500 cP.
[0098] In some embodiments, the grinding fineness of the cathode slurry composition is no greater than 20 µm, or no greater than 15 µm, or no greater than 10 µm, or no greater than 8 µm, or no greater than 5 µm, or 1–15 µm, or 1–10 µm, or 1–5 µm. It is typically determined using a “Hegman” or “grinding” gauge. Grinding fineness can provide information about the actual size of individual dispersed solid particles, the degree of particle dispersion, and / or the presence of agglomerates or coarse particles. Grinding fineness values can be expressed in µm (0.001 inches) or according to the Hegman scale or the National Standard (NS) scale (ranging from 0 to 8, with the number increasing as the particle size decreases). An applicable technique for determining grinding fineness is described in ASTM D1210-05 (2014), entitled “Standard Test Method for Determining the Fineness of Dispersion in Pigment-Carrier Systems Using a Hegman Gauge.”
[0099] Cathode layer performance: The cathode layer formed from the slurry composition exhibits improved interfacial adhesion, cohesive strength and dimensional stability during electrode processing and battery operation.
[0100] In some embodiments, the cathode layer has a peel adhesion strength between the cathode layer and the current collector of at least 0.5 N / 25 mm, or >0.55 N / 25 mm, or >0.6 N / 25 mm, or 0.5-1.1 N / 25 mm, or 0.5-1.0 N / 25 mm, or 0.5-0.9 N / 25 mm, or 0.55-11.1 N / 25 mm, or 0.55-1.0 N / 25 mm, or 0.55-0.9 N / 25 mm, as determined according to ASTM D903, and the peel test is performed at a peel rate of 200 mm / min.
[0101] In some embodiments, the cathode layer has a peel adhesion strength between the cathode layer and the current collector that is at least 5%, at least 10%, or at least 15% higher than that of a cathode layer without HSBC components, as determined by ASTM D903, and the peel test is performed at a peel rate of 200 mm / min.
[0102] In some embodiments, based on the dry weight of the binder present in the cathode layer, the electrolyte absorption rate of the cathode layer after immersion in electrolyte for 24 hours at room temperature is 6-20 wt%, or 7-15 wt%, or 8-13 wt%. This behavior reflects the combined contribution of the PVDF and HSBC components, where the PVDF restricts dimensional changes and the HSBC component provides elastic flexibility, thereby forming a cathode layer that adapts to electrolyte exposure while maintaining interfacial integrity, mechanical cohesion, and anti-delamination properties.
[0103] The electrolyte absorption rate described in this article is a characteristic of the cathode layer, reflecting the interaction between the binder composition and the electrolyte within the cathode layer.
[0104] Cathode performance: The cathode exhibits improved resistance to delamination, cracking and mechanical failure during electrode processing, winding and battery operation.
[0105] In some embodiments, the cathode exhibits improved mechanical durability as evaluated by a winding test, wherein the cathode is wound onto a mandrel and visually inspected for defects. In some embodiments, after the winding test, >50%, or >60%, or >70%, or >80% of the cathode samples show no visual defects. In some embodiments, 50-100%, or 70-100%, or 90-100% of the samples show no visible cracks, peeling, or delamination after the winding test.
[0106] Battery performance: Batteries containing the cathode described herein can exhibit improved electrochemical performance, including capacity retention and efficiency during cycling.
[0107] In some implementations, the battery containing the cathode described herein exhibits a discharge capacity retention of 60-90%, or 60-85%, or 60-80%, or 70-85%, or 75-85% after 200 cycles, as determined using a coin cell assembled with the cathode and tested on a LanHe CT3002A battery testing system.
[0108] In some implementations, the cell including the cathode described herein has a first coulombic efficiency of >70%, or >80%, or >90%, or >95%, or 70-100%, or 80-99%, or 90-99%, or 95-99%, as determined using a coin cell assembled with the cathode and tested on a LanHe CT3002A cell testing system.
[0109] Analytical methods: The composition, structure and properties of the cathode, cathode slurry composition and binder components described herein can be characterized using the following analytical techniques.
[0110] In some embodiments, the prepared cathode layer is analyzed. In some embodiments, the cathode layer may be obtained from the battery or electrode structure and analyzed, as needed, either directly or after appropriate sample preparation (including removal of electrolyte or separation of components to facilitate determination). Determinations of cathode layers recovered from electrochemical cells can be affected by electrochemical processes and sample handling, and these analyses are interpreted in light of these factors. Such procedures enable the analysis of the cathode layer, the binder composition present therein, and the adhesive and compositional characteristics of the cathode.
[0111] The presence of PVDF in the binder composition can be determined by Fourier transform infrared spectroscopy (FTIR) based on characteristic absorption bands associated with CF bonds. The presence of HSBC components can be identified by NMR spectroscopy, optionally combined with FTIR, including the detection of vinyl aromatic units and hydrogenated diene-derived segments. In some embodiments, these techniques are applied to the cathode layer or the resulting polymer portion.
[0112] The structural features of HSBCs (including the presence of vinyl aromatic blocks and hydrogenated diene-derived blocks) can be characterized by proton nuclear magnetic resonance (¹H NMR) spectroscopy. The polystyrene content of HSBCs can be determined by ¹H NMR spectroscopy based on the integration of signals corresponding to aromatic and aliphatic protons. In some embodiments, the characterization of the polymer structure and composition is performed on the prepared cathode layer or on the polymer sample prior to the introduction of the cathode.
[0113] The ABI of HSBC can be determined by HSQC NMR, where cross-peaks corresponding to vinyl aromatic units in different sequence environments are identified and integrated. Within the M-block of the polymer, HSQC chemical shift correlation is used to distinguish vinyl aromatic units in different sequence environments, including units flanked by vinyl aromatic units along both sides of the polymer chain. The ABI is determined by the relative proportion of these units to the total vinyl aromatic units present in the M-block.
[0114] Molecular weight parameters (including peak molecular weight (Mp)) can be determined using size exclusion chromatography (SEC) with suitable calibration standards (e.g., polystyrene standards). This determination can be performed on a polymer sample or a polymer fraction obtained from the cathode layer.
[0115] The relative proportions of PVDF and HSBC components in the binder composition can be determined or estimated using one or more of the following methods: thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), elemental analysis, or spectroscopic calibration.
[0116] According to ASTM D2196, using a rotational viscometer, at 40s -1 The viscosity of the cathode slurry composition was determined at a shear rate and a temperature of 21–25 °C. The selected shear rate represents the shear conditions encountered in the coating process of electrode fabrication. The solid content can be determined based on the mass of the non-volatile components relative to the total mass of the slurry.
[0117] Electrolyte absorption rate can be determined by measuring the weight increase of a binder-containing film or cathode layer after immersion in a liquid electrolyte for a specified time. In one method, the sample is weighed before immersion, immersed in the electrolyte at room temperature for 24 hours, removed, the surface electrolyte is removed, and the sample is reweighed. The electrolyte absorption rate is calculated as a percentage increase in weight relative to the initial dry weight of the sample containing the binder.
[0118] According to ASTM D903, the peel adhesion strength between the cathode layer and the current collector is determined using a tensile testing machine. A coated electrode sample is adhered to a test panel and peeled at a controlled rate, and the force required to separate the cathode layer from the current collector is recorded. The peel adhesion strength is reported as force per unit width (N / 25 mm). In some embodiments, the sample size is approximately 25 mm × 150 mm, and the test is performed at a peel rate of 200 mm / min.
[0119] Example
[0120] The following examples are not limiting.
[0121] Use the following testing method.
[0122] PVDF is a homopolymer of polyvinylidene fluoride with a molecular weight of 1,000,000 g / mol and a melting temperature of 165℃.
[0123] HSBC is a hydrogenated styrene block copolymer with a (S-EB / SS)2X structure, a peak molecular weight (Mp) of 125 kg / mol, a total polystyrene content (PSC) of 35 wt%, a butene unit content of 71 wt%, a coupling efficiency of 93%, a diblock content of less than 7 wt%, a residual unsaturation (RU) of 0.1 meq / g, and a polystyrene block Mp of 7.2 kg / mol. The M block contains approximately 30% ABI of E / B / S copolymer blocks.
[0124] NMP (solvent) is electronic grade 1-methyl-2-pyrrolidone with a purity of at least 99.9% and a water content of 0-0.03%, determined by Karl Fisher titration.
[0125] The active material is lithium iron phosphate (LiFePO4) powder with a median particle size (D50) of 1.302 µm and a bulk density of 0.72 g / cm³. 3 The carbon content is 1.48%.
[0126] The conductive material is a high-purity, structured carbon black powder with a BET surface area of 62 m² / g.
[0127] Preparation of PVDF binder solution and cathode slurry: The PVDF binder solution was prepared by dissolving PVDF in NMP at room temperature. The solid content of the PVDF binder solution was controlled at 8-10 wt%. The active material and conductive agent were then dispersed into the PVDF binder solution using a planetary centrifugal mixer until a homogeneous mixture was obtained, thereby preparing the cathode slurry. The slurry formulation consisted of active material, conductive agent, and binder solution in a mass ratio of 90:5:5.
[0128] Preparation of PVDF+HSBC binder solution and cathode paste: PVDF binder solution was prepared by dissolving PVDF in NMP at room temperature. HSBC binder solution was prepared by dissolving HSBC in NMP at 80-90℃ for 2 hours. The solid content of each binder solution was controlled at 8-10 wt%.
[0129] A cathode slurry was prepared by dispersing the active material and conductive agent into a PVDF binder solution using a planetary centrifugal mixer until a homogeneous mixture was obtained. Then, an HSBC binder solution was added to the mixture at a weight ratio of 9:1 (PVDF to HSBC), and mixing continued until a homogeneous slurry was obtained. The slurry formulation contained active material, conductive agent, PVDF, and HSBC in a mass ratio of 90:5:4.5:0.5.
[0130] Additional NMP solvent can be added during slurry preparation to promote the dispersion of active materials and conductive agents, and to adjust the slurry viscosity (e.g., 2000-15000 cP) for coating. The viscosities of samples at different shear rates are shown in Table 1. Viscosities were measured at room temperature and various shear rates using an HB-DV-II Brookfield viscometer (see Table 1 below). The final solids content of the slurry was 45-50 wt% according to ASTM D2196.
[0131] Table 1: Slurry Viscosity
[0132]
[0133] The fineness of the slurry was assessed using a fineness meter. Measurements were based on the point along a scale where the slurry no longer formed a continuous film or where individual particles were clearly distinguishable. This point indicated the fineness of the slurry. The fineness of both slurries using PVDF alone with a 90:5:5 mass ratio of active material: conductive material: PVDF and slurries using PVDF and HSBC with a 90:5:4.5:0.5 mass ratio of active material: conductive material: PVDF: HSBC was approximately 5 µm.
[0134] Preparation of electrode film
[0135] The cathode paste was applied onto aluminum foil using a coating rod at a speed of 100 mm / min to form a cathode layer. The wet coating was dried in a vacuum oven to remove NMP solvent. The resulting dry film was calendered (compressed) to a target film thickness of approximately 60–120 µm. The target compaction density was 1.6–2.0 g / cm³. 3 Within the range.
[0136] Peel strength test: Cut the cathode layer on the aluminum foil into strips measuring 150 mm × 25 mm along the coating direction. Use double-sided tape (e.g., 3M) to secure the coated surface of each sample to the stainless steel peel test plate. Take care to avoid air bubbles and ensure uniform adhesion between the sample and the test panel.
[0137] Peel strength was tested using a tensile testing machine at a peel rate of 200 mm / min, and the peel force was recorded. This test method is based on the principle of ASTM D903, with modifications made to the sample size and peel rate to suit the electrode material requirements.
[0138] As described above, the cathode layer is prepared from a cathode slurry containing 45 wt% PVDF-based formulation and 47.4 wt% PVDF+HSBC-based formulation.
[0139] Table 2: Peel Strength
[0140]
[0141] Electrolyte absorption rate (weight gain) of adhesive films: The electrolyte absorption rates of HSBC and PVDF were evaluated by measuring the weight gain after immersion. The polymer films were prepared by hot-pressing at 180°C for 5 minutes. The resulting polymer sheets were cut into 25 x 25 mm samples, with HSBC sheets having a thickness of 1.70–1.80 mm and PVDF sheets having a thickness of 0.60–0.65 mm. Three samples were prepared for each polymer.
[0142] Weigh the samples and then immerse them in an electrolyte solution (1.0 M LiPF6 dissolved in ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) in a 1:1:1 volume ratio) at room temperature for 24 and 48 hours. After immersion, remove the samples, remove the surface electrolyte, and reweigh the samples. Calculate the weight gain for each sample and take the average over the three samples.
[0143] After 24 hours of soaking, the average weight of the HSBC samples increased by 11 wt%, while the average weight of the PVDF samples increased by 5 wt%. After 48 hours of soaking, the average weight of the HSBC samples increased by 14 wt%, while the average weight of the PVDF samples increased by 12 wt%.
[0144] The volumetric expansion of the polymer sheet was not directly measured due to sample deformation after electrolyte exposure, making dimensional measurements unreliable. Instead, electrolyte absorption was assessed based on weight gain. The measured weight gain reflects the interaction between the electrolyte and the polymer and provides an indication of relevant dimensional changes and solvent compatibility.
[0145] Battery assembly and application performance testing
[0146] CR2032 coin cells were assembled for electrochemical performance testing. Cathode electrode samples were cut into 14 mm diameter disks and baked at 60 °C for 12 hours before assembly. The cathode disks were used as the working electrode, and lithium metal was used as the counter and reference electrodes. Celgard 2500 (porous polypropylene film) was used as the separator. The areal loading of the PVDF-based cathode was approximately 8.5–9.0 mg / cm², and that of the HSBC-based cathode was 9.2–10.0 mg / cm².
[0147] The electrolyte is 1.0 M LiPF6 (lithium hexafluorophosphate), dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 1:1), or dissolved in EC / DEC / dimethyl carbonate (DMC) (volume ratio 1:1:1), depending on the test conditions. Approximately 90 µL of electrolyte is added to each coin cell.
[0148] All button cells were assembled in an argon-filled glove box with water and oxygen concentrations below 0.1 ppm. After assembly, the cells were conditioned at room temperature (18–25 °C) for 12 hours prior to electrochemical testing. The cycling performance and rate capability of each cell were then evaluated under specified current conditions between 2.5 and 3.65 V.
[0149] Cyclic performance tests were performed on the LanHe CT3002A battery testing system. Before testing, the button cells were left at room temperature for 10 minutes. Each cell was then cycled between 2.5 and 3.65V.
[0150] Each cycle consists of charging to 3.65V with a constant current of 1 / 3C, then maintaining the voltage to a cutoff current of 0.02C, and discharging to 2.5V with a discharge of 1 / 3C.
[0151] Record the initial charge capacity and initial discharge capacity. Capacity retention is calculated as the ratio of the discharge capacity after a given number of cycles to the initial discharge capacity. The first coulombic efficiency is calculated as the ratio of the initial discharge capacity to the initial charge capacity.
[0152] The C-ratio is calculated based on the measured initial discharge capacity of the battery.
[0153] The cathode layer used in the button cell is prepared from a slurry with a solid content of 45 wt% and 47.4 wt%, as described above.
[0154] Table 3: Cyclic Performance
[0155]
[0156] Table 4: C-ratio performance
[0157]
[0158] As shown in Table 2-4, the introduction of HBSC improves the peel adhesion to the current collector and enhances the processability of the slurry, while maintaining comparable electrochemical performance, including capacity and rate capability. In some embodiments, the introduction of HSBC improves adhesion and rheology without negatively impacting electrochemical performance.
[0159] Table 5: Summary of discharge voltage of button cells under different C-ratios
[0160]
[0161] The cathode electrode was wound five times onto a mandrel (0.7 mm in diameter) and visually inspected for cracks, spalling, and other defects. Ten samples were tested, and the number of samples without visual defects was recorded. The percentage of samples without visual defects is shown in Table 6 below. The thickness shown after rolling is the final dry film thickness after multiple rolling passes.
[0162] Table 6: Winding Test – Percentage of Specimens Without Visual Defects
[0163]
Claims
1. A cathode for a battery, comprising a current collector and a cathode layer disposed on the current collector; The cathode layer comprises an active material, a conductive material, and a binder composition, wherein the binder composition comprises: Polyvinylidene fluoride, The hydrogenated styrene block copolymer component comprises a first hydrogenated styrene block copolymer having at least one of the general formulas selected from AMA, (AMA)nX, (AM)nX, and mixtures thereof, wherein n is an integer from 2 to 7, X is a residue of a coupling agent, each A block consists of a vinyl aromatic unit, each M block consists of at least one conjugated diene unit and at least one vinyl aromatic unit, and the aromatic block index of the M block, as determined by HSQC NMR spectroscopy, is 3-40%. The first hydrogenated styrene block copolymer has a peak molecular weight (Mp) of 80-150 kg / mol and a polystyrene content of 20-70 wt%. The weight ratio of the polyvinylidene fluoride to the hydrogenated styrene block copolymer component is 4:6-15:1; The peel adhesion strength of the cathode layer to the current collector is >0.5 N / 25 mm, as determined by ASTM D903, and the peel test is performed at a peel rate of 200 mm / min.
2. The cathode according to claim 1, wherein the M block is selected from E / B / S and EP / S, wherein each E / B / S block is a copolymer block composed of ethylene units, butene units and vinyl aromatic units, and each EP / S block is a copolymer block composed of ethylene-propylene units and vinyl aromatic units.
3. The cathode according to claim 1, wherein the first hydrogenated styrene block copolymer has at least one general formula selected from SE / B / SS, (SE / B / SS)nX, (SE / B / S)nX, S-EP / SS, (S-EP / SS)nX, (S-EP / S)nX, and mixtures thereof, wherein n is an integer from 2 to 7, X is a residue of a coupling agent, each S block is composed of vinyl aromatic units, each E / B / S block is a copolymer block composed of ethylene units, butene units and vinyl aromatic units, and each EP / S block is a copolymer block composed of ethylene-propylene units and vinyl aromatic units.
4. The cathode according to claim 3, wherein the first hydrogenated styrene block copolymer has the general formula (SE / B / SS)nX and has a peak molecular weight of 90-140 kg / mol.
5. The cathode according to claim 1, wherein the first hydrogenated styrene block copolymer has a polystyrene content of 30-45 wt%.
6. The cathode according to claim 1, wherein the first hydrogenated styrene-based block copolymer is modified by grafting with maleic anhydride.
7. The cathode according to claim 1, wherein the first hydrogenated styrene block copolymer has a butene unit content of 20-80 wt% relative to the total diene-derived units.
8. The cathode according to claim 1, wherein the hydrogenated styrene block copolymer component further comprises a second hydrogenated styrene block copolymer having the general formula AD, wherein each A block is composed of a vinyl aromatic unit and each D block is composed of a conjugated diene unit; and wherein the weight ratio of the first hydrogenated styrene block copolymer to the second hydrogenated styrene block copolymer is 1:1 to 3:
1.
9. The cathode according to claim 8, wherein the second hydrogenated styrene block copolymer component has a structure selected from SE / B, S-EP, and mixtures thereof, wherein each S block is composed of vinyl aromatic units, each E / B block is a copolymer block composed of ethylene / butene units, and each EP block is a copolymer block composed of ethylene-propylene units.
10. The cathode according to any one of claims 1-9, wherein the cathode layer has an active material: a conductive material: polyvinylidene fluoride: hydrogenated styrene block copolymer component in a mass ratio of 72:4.0:3.6:0.4 to 108:6.0:5.4:0.
6.
11. The cathode according to any one of claims 1-9, wherein after immersion in a liquid electrolyte at room temperature for 24 hours, the cathode layer exhibits an electrolyte absorption rate of 7-15 wt%, based on the dry weight of the binder present in the cathode layer.
12. The cathode according to any one of claims 1-9, wherein the peel adhesion strength between the current collector and the cathode layer, as determined by ASTM D903, is at least 5% higher than the peel adhesion strength of the cathode layer without the hydrogenated styrene block copolymer component.
13. The cathode according to any one of claims 1-9, wherein the current collector is treated, roughened, or coated with a carbon or oxide layer.
14. The cathode according to any one of claims 1-9, wherein the binder composition is dissolved or dispersed in a solvent selected from the group consisting of N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethyl sulfoxide, dimethylformamide, dimethylacrylurea, γ-butyrolactone, dimethylacetamide, acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, ethyl acetate, butyl acetate, tetrahydrofuran, dioxane, and mixtures thereof.
15. The cathode of claim 14, wherein the slurry has at least one of the following properties: Viscosity of 2000-15000 cP, according to ASTM D2196 at 21-25°C and 40 s -1 The shear rate was measured. Solid content is 40-75 wt%; and The grinding fineness is no greater than 10µm.
Citation Information
Patent Citations
Process for the preparation of modified block copolymers
US4292414A
Selectively hydrogenated block copolymers modified with acid compounds or derivatives
US4578429A
Thermoplastic elastomers of isobutylene and process of preparation
US4946899A
High impact resistant blends of thermoplastic polyamides and modified block copolymers
US5506299A
Block copolymers and method for making same
US7169848B2